Emancipazione e Diritti Umani nel Pensiero di Boaventura de Sousa Santos - Guarino, Carmela (Utopía y Praxis Latinoamericana)
Boaventura de Sousa Santos makes a minute analysis of current society in which values such as equality and fraternity are eclipsed by the logic of neoliberal capitalism. Law and modern science have contributed to this phenomenon through the determination of societies ever more unjust and excluding. The remedy for an imminent defeat, considers De Sousa Santos, is social emancipation, that is, an encounter between different civilizations, a process that permits mutual understanding among world citizens; therefore the concept of difference cannot be considered as a factor of separation and isolation, but rather as a factor of interchange and solidarity.